Reversible Inactivation of the Dorsal Raphe Nucleus Increases Morphine-Induced Antinociception in Tolerated but not in Nontolerated Rats - Sarihi, A.; Heshmatian, B.; Pahlevani, P.; Komaki, A.; Haghparast, A. (Нейрофизиология, 2015)
We examined possible effects of the state of the dorsal raphe nucleus (DRN) on morphineinduced antinociception in morphine-tolerated and nontolerated rats. Stereotaxically, lidocaine (2%) was applied to the DRN for its reversible inactivation. On the test day, all animals received 10 mg/kg morphine 10 min before the tail-flick test (induction of thermal acute pain), and the maximum antinociceptive effect (MPE) was measured. In the morphinetolerated group, animals preliminarily received everyday introductions of 20 mg/kg morphine for four consecutive days. There was a significant increase in the MPE (%) in the lidocainetreated group (with inactivation of the DRN) compared to the control group. However, there was no significant difference in morphine-induced antinociception between the saline- and lidocaine-treated groups. Nonetheless, the antinociceptive responses to morphine (MPE) in morphine-tolerated rats were more significant in animals treated with lidocaine compared to the control group. Our results suggest that lack of GABA in the locus coeruleus, which follows inhibition of serotonin release in the DRN during ablation, may cause adrenergic cellinduced analgesic effects.